Huge (Voluminous) Femoral hernia in a male (Case Report) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Femoral hernia is usually of a small size. It is more common in females than males and presents in a strangulation. It is considered a huge (Voluminous) if it exceeds a volume of a fist.Herewith, A 54-year-old thin man presents with an irreducible but non-strangulated huge right femoral hernia. Diagnosis was confirmed by history and physical examination. Preoperative laboratory and chest x-ray were normal.  Open mesh repair was done with uneventful postoperative course. The patient was well after 18 months of operation without recurrence.